Adoption and implementation of HPV self-collection sampling by CHWs in Jujuy, Argentina - Mariana Curotto; Julieta Zalacaín-Colombo; Melisa Paolino; Silvina Arrossi (Instituto Nacional de Salud Pública, 2018)
Objective. To evaluate adoption and implementation of scaling up of HPV self-collection (SC) strategy offered door-to-door by Community Health Workers (CHWs) in Jujuy, Argentina. Materials and methods. A self-administered questionnaire was applied to 478 CHWs. RE-AIM model was used to evaluate adoption and implementation dimensions. Results. Adoption: 81.8% offered SC and 86.4% were satisfied with the strategy. Implementation: main problems were delays in the delivery of tubes (61.3%) and results (70.0%), lack of human resources (28.3%) and difficulties in obtaining an appointment for triage (26.1%). The main obstacle was the excessive workload of CHWs (50.2%). Training (38.0%) and the list of women to be offered the test (28.7%) were identified as facilitators. Conclusions. The adoption of SC strategy was high among CHWs. Program strategies should be strengthened to motivate and reduce the excessive workload of CHWs when implementing SC strategy.